PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA KOPERASI UNIT DESA (KUD) KAMPAR KECAMTAN KAMPA KABUPATEN KAMPAR - Khairu Rahmat; Gusnardi Gusnardi; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of service quality on thesatisfaction of members of the village unit cooperative (KUD) Kampar, Kampa District,Kampar Regency. This research is a research based on a quantitative approach, thepopulation of this determination is 88 cooperative members who were selected using thesample random sampling method. The data collection technique used questionnaire . Thedata analysis used simple regression analysis. The results of this study indicate that thequality of service has an effect on the satisfaction of members of the village unitcooperative (KUD) Kampar, Kampa District, Kampar Regency.Keywords: service quality, Member Satisfaction